Subcutaneous Recombinant Hirudin (HBW 023) Versus Intravenous Sodium Heparin in Treatment of Established Acute Deep Vein Thrombosis of the Legs: a Multicentre Prospective Dose-ranging Randomized Trial - Schiele, François; Lindgaerde, Folke; Eriksson, Henry; Bassand, Jean-Pierre; Wallmark, Anders; Hansson, Per-Olaf; Grollier, Gilles; Sjo, Malvin; Moia, Marco; Camez, Anne; Smyth, Vince; for the International Multicentre Hirudin Study Group; Walker, Michael (Thrombosis and Haemostasis, 1997)
The aim of this multicentre, prospective, randomised, dose-ranging study was to compare the safety and efficacy of subcutaneous recombinant hirudin (HBW 023) against intravenous sodium heparin in acute lower limb deep venous thrombosis (DVT). Patients were randomized to treatment with either HBW 023 or heparin for 5 ±1 days. HBW 023 was given according to body-weight in three dose groups. Thromboembolic disease was assessed by phlebography and ventilation/perfusion (V/Q) scanning on Bay 1 and Day 5±1. One hundred and fifty-five patients were enrolled, of these 121 were evaluable for efficacy analysis. Significantly fewer patients on HBW 023 developed new V/Q abnormalities during the treatment period, (p = 0.006). There was no difference between the groups in thrombus extension or regression, major bleeding complications or serious adverse events. There were significantly fewer findings of new V/Q mismatch after treatment with HBW 023, and anticoagulant control was superior in these patients.